FEEDING BEHAVIOUR OF RED PUMPKIN BEETLE, AULACOPHORA FOVEICOLLIS (LUCAS) ON LEAF EXTRACTS OF DIFFERENT CUCURBITS - MIEHITA, P.K.; SANDHU, G.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
In feeding bioassays, application of crude cucurbitacin extracts from watermelon and muskmelon on relatively non-preferred cultivars (sponge gourd and bottle gourd), induced preference for feeding by red pumpkin beetle on non-preferred cultivars. The redpumpkin beetle adults demonstrated a distinct preference for cotyledons of non-preferred cultivar treated with crude cucurbitacin extracts as apparent from significantly increased leaf injury. When crude cucurbitacin extracts were offered to red pumkin beetles on filter paper discs, significantly more feeding was observed on treated discs as compared to untreated ones. This clearly demonstrated that cucurbitacin primarily act as arrestant and feeding stimulants for red pumpkin beetle.